The location of egg masses of Ostrinia nubilalis [Lepidoptera : Pyralidae] on potato plants - Dornan, A.P.; Stewart, J.G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
The location of egg masses of the European corn borer, Ostrinia nubilalis, was studied on potatoes (Solanum tuberosum) “Russet Burbank” grown on Prince-Edward-Island, Canada, from 1990 to 1992. The within-plant positions of 315 egg masses were characterized by the examination of approximately 3700 plants. Ninety-two percent of the egg masses were found on the bottom two-thirds of the plants and 95% were found on the underside of the leaflets and on the stalks. In total, 88% of the egg masses were found on the bottom two-thirds of the plants on both the stalks and the underside of the leaflets. Sampling time can be optimized if the people engaged in scouting programs concentrate their efforts on the bottom two-thirds of the stalks alone, which represents only 3.7% of the total surface area of the haulm but contains 50% of the egg masses.